THE APPLICATION OF 4C COMPETENCIES IN ENGLISH SUBJECT ON THE SECOND GRADE OF SMAN 1 MAROS - Nurul Saqina Anwar; Kisman Salija; Nur Aeni (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
The aim of this study was to describe the application of 4C competencies to English lessons in the second grade of SMAN 1 Maros and to know the English score of the second grade of SMAN 1 Maros during the application of 4C competencies. The researcher applied descriptive qualitative method. The data of this research were collected through observation, interview, and documentation. This article only consists of the formulation of the first problem which was collected through the interview session. The subjects of this study were English teachers who teaches in the second grade and the second-grade students of SMAN 1 Maros that was consisted of two classes, but in this article the researcher only describe one class. The result of data analysis found that the application of 4C competencies in the second grade of SMAN 1 Maros has been implemented very well by the teachers and the students in the classroom.